Enhancing Corporate Management - A Case of Saigon Hanoi Bank in Vietnam Under Impacts of Macro Indicators - HA, TRAN THI HOANG; HUY, DINH TRAN NGOC; ANH, PHAM TUAN (The journal of contemporary issues in business and government, 2021)
Bank is a special corporation and plays a vital role in economic circulation. In order to achieve sustainable bank management in emerging markets such as Vietnam, this paper measures bank management capabilities in famous model under impacts of both macro internal and external variables during low inflation time 2015-2020 in the country. During covid 19 and US-China commerce war, analyzing these impacts to have a netter management plans are necessary for commercial banks to respond to economic recession and impacts from trade war. In recent years, research scholars link banking sustainability with CSR and community and environment; however this study takes another macro approach to banking sustainability. This research paper aims to figure out what are recommendations to management better bank performance to respond to fluctuation sin macro conditions under the case of one of big listed Vietnam commercial bank, Saigon Hanoi Bank (SHB) during the low inflation period 2015- 2020 with stock price weekly data. We use an econometric model with Eviews to estimate impacts from 9 macro variables on Beta CAPM. We find out that bank management team need to pay attention to macro contex in which increasing VNIndex and lending rate and Risk free rate. Then, one of its major findings is the suggestion of macro and risk management policies for bank and relevant government agencies. Our recommendation can be used for reference in many other developing markets. JEL classification numbers: M21, M1, G12, G30